Usefulness of Tissue Doppler Imaging for the Evaluation of Pulmonary Hypertension in Canine Heartworm Disease - Jorge Isidoro Matos; Sara Nieves García-Rodríguez; Noelia Costa-Rodríguez; Alicia Caro-Vadillo; Elena Carretón; José Alberto Montoya-Alonso (Animals, 2023)
Background: Dirofilaria immitis is a nematode that produces proliferative pulmonary endarteritis in dogs due to direct contact of the adult parasites with the intima layer of the pulmonary arteries, leading to irreversible severe structural damage and sustained pulmonary hypertension (PH), which can produce severe cardiorespiratory disorders. The purpose of this study was to assess the diagnostic value of the echocardiography tissue Doppler imaging (TDI) in determining the presence of PH in dogs with heartworm disease. Methods: There were 116 heartworm-infected dogs with PH and 33 healthy dogs included in the study. Based on the right pulmonary artery distensibility index (RPADi) < 29.5%, PH was present in 47.4% of infected dogs. Additionally, the animals were evaluated using other standard alternative echocardiographic measures to estimate PH. Moreover, a total of eight echocardiographic measurements were analysed using the TDI to determine its usefulness in diagnosing PH (E′, A′, S, E′:A′, global TDI, HRI-IVCT, HRI-IVRT, R-TEI). Results: The TDI measurements showed significant differences between dogs with and without PH, demonstrating a positive correlation with respect to the RPADi. In addition, cut-off values for the detection of PH with excellent sensitivity and specificity were found for E′:A′, global TDI, HRI-IVCT, HRI-IVRT and R-TEI. Conclusions: The TDI mode may be useful as an adjunct diagnostic method for the determination of PH in dogs with Dirofilaria immitis.